Parental experiences on adolescent expressions of respect in low-income families - Azarcon, Frances Mikaela V.; Epres, Ma. Krissia Tedelyn P.
The study aimed to explore parental expectations, observations, and feelings regarding the adolescent childs expressions of respect towards 30 parents of low income families from Quezon City. Respondents were chosen through a purposive sampling technique. Data was gathered by conducting indepth interviews, which were later transcribed and coded according to salient themes. Results revealed that parents define respect as a concept and an action. Parents also reported reasons for expecting respect and ways by which they expect to be respected. Adolescents were reported to typically meet these expectations by practicing the parents expected expressions of respect. In response, parents reported feeling either positive or negative feelings towards these expressions. With the findings of this study, the cultural value of respect can be investigated deeper by delving into the perspective of both parents and their respective adolescent child and exploring their relationship as that can yield different results regarding the parental experiences on adolescents expression of respect. With that, Filipinos of different fields of expertise may use these findings to understand and improve the Filipino family as family remains central throughout a persons life.